Perancangan Bangunan Kapal General Cargo 17000 Dwt Untuk Rute Pelayaran Jakarta - Semarang - Sulaiman Ali; Ramadhani Japri (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
General cargo ship is a ship that carries various kinds of cargo in the form of goods. Goods that are transported are usually packaged goods. General cargo ships are equipped with cargo cranes to make loading and unloading easier. In this design the hull design is planned. The main size of the ship was obtained using a regression comparison method based on data from 2 comparison vessels obtained from the Korea Register of Shipping (KRS). From the main dimensions obtained, a line plan and hydrostatic analysis is carried out according to the IMO standard. From the planning results obtained for ships with a capacity of 17000 DWT obtained ship dimensions with length over all (LOA) 153.45 m, length between prependiculars (LBP) 144.24 m, Length on load waterline (LWL) 147.85 m, width (B ) 25.27 m, height (H) 13.5 m, loaded (T) 9.52 m, speed (Vs) 14.75 knots, block coefficient (Cb) 0.7, midship coefficient (Cm) 0.79 , waterline coefficient (Cw) 0.81, horizontal prismatic coefficient (Cph) 0.91, vertical prismatic coefficient (Cpv) 0.89, volume 25520.5 m3. This comparison ship method makes it easy for ship designers with accurate results.